Sap flow scaling and crop coefficient of dry-farmed olive orchards converted to irrigation - Santos, Francisco Lúcio (2012)
Tree water uptake is often estimated based in a crop coefficient kc, a ratio of the tree water uptake and a reference evapotranspiration, ET0. The concept behind estimating tree crop coefficient implies that data should be representative of the population of trees analyzed. Ideally it would require the monitoring of a large number of trees in each treatment population. This paper reports on a scaling method to establish stand-level transpiration estimates and crop coefficients from individual sampled tree sap flow measurements. The scaling technique was implemented for individual tree sap flow measurements on the following irrigation treatments: A, fully-irrigated; B, irrigated to provide for approximately 60% of crop evapotranspiration; C, irrigated to provide for 100% of crop evapotranspiration during three critical phase periods: before-flowering, at beginning of pit-hardening and before crop-harvesting, and dry-farming treatment D. Results show that stand transpiration T depart from individual tree transpiration values. They consequently were used to establish crop, kc and water stress, ks coefficients to account for the cluster’s characteristics and degree of tree’s water uptake. Using the individual tree transpiration rates would be less appropriate.